2009
DOI: 10.5194/acpd-9-10101-2009
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Trace gas and particle emissions from domestic and industrial biofuel use and garbage burning in central Mexico

Abstract: Abstract. In central Mexico during the spring of 2007 we measured the initial emissions of 12 gases and the aerosol speciation for elemental and organic carbon (EC, OC), anhydrosugars, Cl-, NO3-, and 20 metals from 10 cooking fires, four garbage fires, three brick making kilns, three charcoal making kilns, and two crop residue fires. Biofuel use has been estimated at over 2600 Tg/y. With several simple case studies we show that cooking fires can be a major, or the major, source of several gases and fine partic… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
70
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(83 citation statements)
references
References 61 publications
9
70
4
Order By: Relevance
“…Direct emissions include garbage burning (7), incineration of municipal and medical wastes, burning of biomass, agricultural products and coal, and industrial processes, e.g., semiconductor and petroleum manufacturing (5). Natural sources in air include volcanic eruptions and reactions of sea salt and organochlorine compounds (5).…”
mentioning
confidence: 99%
“…Direct emissions include garbage burning (7), incineration of municipal and medical wastes, burning of biomass, agricultural products and coal, and industrial processes, e.g., semiconductor and petroleum manufacturing (5). Natural sources in air include volcanic eruptions and reactions of sea salt and organochlorine compounds (5).…”
mentioning
confidence: 99%
“…But the subsequent decrease in simulated POA reversed at 17:00 UTC (11:00 LT) instead of continuing to decrease for four more hours during the afternoon. As discussed previously with CO and EC, there are likely uncertainties in the local emissions that may contribute to errors on POA at this site, including brick kilns (Christian et al, 2009) and other local sources.…”
Section: Organic Mattermentioning
confidence: 99%
“…Recently Christian et al (2009) suggested that trash burning at municipal landfills could be responsible for about 29% of the PM 2.5 present in the urban Mexico City area. However, their estimate has a high uncertainty, since it is based on extrapolating measurements from four short-term trash burning events and the use of antimony (chemical symbol Sb) as a tracer for trash burning.…”
Section: Emission Inventoriesmentioning
confidence: 99%
“…In addition, numerous small-scale enterprises such as brick kilns burn a variety of fuels including garbage, crop waste, tires, used motor oil, scrap wood, sawdust, and charcoal (Le and Oanh, 2010). Although an inventory of these fuel-intensive enterprises has not been performed in SEA, such informal operations account for up to 50% of non-agricultural employment in some similar economic areas over the globe (Christian et al, 2010).…”
Section: Social Geographymentioning
confidence: 99%